An explanation for high-frequency broadband electrostatic noise in the Earth's magnetosphere - Moolla, S.; Bharuthram, R.; Singh, S.V.; Lakhina, G.S.; Reddy, R.V. (My University, 2007)
[1] A parametric study of high-frequency nonlinear electrostatic oscillations in a magnetized plasma consisting of hot electrons, cool electrons, and cool ions has been conducted. The fluid equations have been used for each species, and the coupled system of differential equations in the rest frame of the propagating wave have been numerically solved to yield the electric field for parameters characteristic of the auroral region. The effect of the initial driving amplitude, cold and hot electron densities, propagation angle, hot electron drift, and cool electron and cool ion temperatures on the electric field structures have been investigated and, in particular, the frequency and the type of electric field structure (sinusoidal, sawtooth, or spiky). The initial driving amplitude as well as the cold and hot electron densities are shown to affect the nature (sinusoidal, sawtooth, or spiky) of the waveforms, with a transition from linear sinusoidal waveforms for low initial driving amplitude, to spiky, nonlinear waveforms for larger values of the initial driving amplitude. In addition, the drifts of the species are shown to play a crucial role in the periods of the waveforms, while the temperatures of the electron species are also shown to vary the periods of the waveforms but not as much as in the case of the drifts of the species. The results show a strong resemblance to satellite observations of the different types of broadband electrostatic noise reported, which are nonlinear, spiky structures of varying amplitude and period.
Keywords: Solitary waves; Spiky; Electron acoustic; Electron cyclotron; Magnetosphere; BEN; Electric field